Analysis of the frequency and duration of the clinical remission phase in type 1 diabetes - Todorov Teodora; Stojanović Aleksandar; Miličić Tanja (Medicinski Podmladak)
Introduction: Clinical remission (CR) phase, in other words, euglycaemia, in the absence of insulin therapy (complete CR) or with a reduced daily dose of insulin (partial CR) can be achieved in some patients with new-onset type 1 diabetes (T1D) after the introduction of insulin therapy. Unfortunately, there is still not enough information about the factors influencing the induction and duration of remission. Material and methods: This research included 62 patients with the diagnosis of new-onset T1D, who were treated at the Clinic of Endocrinology, Diabetes and Metabolic Diseases, University Clinical Centre of Serbia in 2019 and 2020. Demographic, clinical and laboratory data were acquired from medical records. Descriptive statistical methods, Fisher's exact probability test, Pearson's chi-square test, Student's t test, Mann Whitney U test and Spearman's correlation coefficient were used for statistical analysis. Results: Clinical remission was inducted in 46.8% of patients and its average duration was 11.2 months. Patients with CR had remarkably lower HbA1c values (9.9 ± 2.8 vs 11.8 ± 2.4%; p=0.007) and lost less weight (4 vs 12 kg, p<0.001) compared to patients without CR. Additionally, C peptide levels at the beginning and 6 minutes after the glucagon test were remarkably higher in patients with CR compared to patients without CR (p<0.001). At the same time, remarkably more patients with CR had autoantibodies detected compared to those without CR (GAD 100% vs 72.4% i IA2-2A 81.8% vs 34.5%; p=0.001). The duration of CR was remarkably correlated with the level of C peptide at the beginning and 6 minutes after the glucagon test (p<0.001). Conclusion: Patients with CR (46.8%) had better metabolic control, less weight loss, better endogenous insulin reserve capacity and less frequent presence of autoantibodies to beta cell antigens at disease onset. At the same time, the duration of CR was associated with an initially better, preserved, endogenous insulin reserve.